Data set of dissolved major and trace elements from the lacustrine systems of Clearwater Mesa, Antarctica - Lecomte, Karina Leticia; Echegoyen, Cecilia Vanina; Vignoni, Paula A.; Kopalová, Katerina; Kohler, Tyler J.; Coria, Silvia Herminda; Lirio, Juan Manuel (Data in Brief)
This article presents analytical observations on physicochemical parameters and major and trace element concentrations of water, ice, and sediment samples from the lake systems of Clearwater Mesa (CWM), northeast Antarctic Peninsula. Geochemical analyses include inductively coupled plasma mass spectrometry (ICP-MS) for cations and trace elements and ion chromatography for anions. Some figures are included (i.e. Piper and Gibbs diagrams) which indicate water classification type and rock-water interactions in CWM, respectively. It also contains PHREEQC software output, listing the chemical speciation for dissolved elements, Saturation Indexes (SI), and modelling outputs. Each lake SI are also illustrated in a figure. Finally, total organic and inorganic carbon (TOC and TIC, respectively) were determined for bottom lake sediments and marginal salt samples. This information will be useful for future research assessing the impacts of anthropogenic pollution and the effects of climate change, providing insights into naturally occurring geochemical processes in a pristine environment, and evaluating geochemical behaviour of dissolved elements in high-latitude hydrological systems. These data correspond to the research article “Dissolved major and trace geochemical dynamics in Antarctic Lacustrine Systems” [1]. Fil: Lecomte, Karina Leticia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Echegoyen, Cecilia Vanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Vignoni, Paula A. Universitat ...